An evaluation of the social work education program in Thailand - Sudaratana Suphaphiphat 1942- (1987)
This study examined the development of the social work education program in Thailand and evaluated the effectiveness of the undergraduate social work education program of Thammasat University. It provides feedback information which can be used for the improvement of the undergraduate social work education program in Thailand.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Social work education -- Thailand